2012
DOI: 10.1134/s1062360411040059
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of cells of apical meristems and realization of gametophytic apomixis in flowering plants

Abstract: Based on our own and literature data on peculiarities of caryotypical variability, we concluded that gametophytic apomixis is naturally accompanied with phenomena of poly , aneu , and mixoploidy and that apomicts have genome instability manifesting at the level of meristematic somatic cells. In this connection, a hypothesis is substantiated that realization of this mode of seed reproduction in flowering plants is caused by modification of systems of cell cycle control, following after acts of hybridogenesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…antarctica populations is maintained by its capacity of vegetative and/or apomictic propagation [ 14 ; 52 ]. It has been shown that apomixis is accompanied with phenomena of poly-, aneu-, and mixoploidy in flowering plants [ 53 , 54 ]. Also, a high level of aneuploidy has been found in plant species propagated asexually [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…antarctica populations is maintained by its capacity of vegetative and/or apomictic propagation [ 14 ; 52 ]. It has been shown that apomixis is accompanied with phenomena of poly-, aneu-, and mixoploidy in flowering plants [ 53 , 54 ]. Also, a high level of aneuploidy has been found in plant species propagated asexually [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…We focused our analyses on documented cases in animals, but this phenomenon may be widespread in plants. Indeed, hybridogenesis has been observed in plants that undergo genome exclusion after a hybridization event (Kashin ; Dubovets & Sycheva ). The appearance of selfish genetic elements, resulting in meiotic drive, has also been registered in plants (Nasuda et al.…”
Section: Discussionmentioning
confidence: 99%